Relationship between maximum dynamic strength of the lower limb with sprint and vertical jump in amateur soccer players (Revista Chilena de Rehabilitación y Actividad Física, 2025)
Objective: The present study aimed to evaluate and describe whether there is a relationship between lower limb strength in 1RM free weight squat with sprint, SJ and CMJ in amateur soccer players. Methodology: Quantitative-correlational crosssectional study. The sample was selected in a non-probabilistic manner for convenience with the aim of evaluating and describing whether there is a relationship between lower limb strength in 1RM free weight squat with sprint, SJ and CMJ in amateur soccer players. 23 amateur soccer players participated, all members of the Colo Colo de San Javier Sports and Social Club (ANFA) VII region, Chile. Conclusion: This study shows that 1RM squat strength levels are not related to sports variables in amateur soccer players in SJ and Sprint, but are related to CMJ jump.
Keywords: Soccer; Muscle Strength; Athletic Performance; Sports Nutritional Sciences; Acceleration; Exercise